Daily field checking list by Walter Rosene, September 11, 1932 - Rosene, Walter M., Sr., 1880-1941et al
Bird checklist dated September 11, 1932. This checklist was used by Walter Rosene to record birds sighted around Adix Ponds and Adix Woods between 8:30 and 11:30. Plustek--flatbed